LDL-Based Lipid Nanoparticle Derived for Blood Plasma Accumulates Preferentially in Atherosclerotic Plaque - Boada, Christian A.; Zinger, Assaf; Rohen, Scott; Martinez, Jonathan O.; Evangelopoulos, Michael; Molinaro, Roberto; Lu, Madeleine; Villarreal-Leal, Ramiro Alejandro; Giordano, Federica; Sushnitha, Manuela; De Rosa, Enrica; Simonsen, Jens B.; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
Targeting nanotherapies aimed directly to atherosclerotic plaques could be an efficient strategy to treat cardiovascular diseases. In this work, we have synthesized a biomimetic nanoparticle (NPs) that we have called "aposomes" comprised of the major low-density lipoprotein (LDL) protein, apolipoprotein B-100 (apoB-100), at the surface of a liposomal phospholipid bilayer. The aposomes were synthesized from LDL isolated from plasma using a microfluidic micromixing approach. The synthesized aposomes had a diameter of 91 nm  4 nm and a neutral surface charge of 0.7 mV  mV. Protein analysis using western blot and flow cytometry confirmed the presence of apoB-100 on the surface of aposomes. Interestingly, aposomes retained the drug loading capabilities of liposomes demonstrating a prolonged release curve with ~80% cargo release at four hours. Considering the natural tropism of LDL towards the atherosclerotic plaques, we evaluated the biological properties of aposomes in a mouse model of advanced atherosclerosis. We observed a ~20-fold increase in targeting of plaques when comparing aposomes to control liposomes. Additionally, aposomes presented a favorable biocompatibility profile that showed no deviation from normal values in liver toxicity markers (i.e., LDH, ALT, AST, Cholesterol). The synthesis of this platform is a new milestone in microfluidic synthesis of bio-hybrid nanoparticles (NP), transforming liposomes into targeted biomimetic ApoB-100 NP in a simple and rapid fashion. To our knowledge, this study represents the first instance of a NP delivery system that targets atherosclerotic plaque by making a hybrid NP from LDL isolated from blood plasma using microfluidics.